Deposition of calcium phosphate coatings using radio frequency magnetron sputtering of substituted β-tricalcium phosphate targets; Journal of Physics: Conference Series; Vol. 1115 : 6th International Congress "Energy Fluxes and Radiation Effects". 14th International Conference on Modification of Materials with Particle Beams and Plasma Flows (14th CMM) - Fedotkin A. Yu. Aleksandr Yurjevich; Bolbasov E. N. Evgeny Nikolaevich; Kozelskaya A. I. Anna Ivanovna; Useinov A. S. Aleksey Serverovich; Tverdokhlebov S. I. Sergei Ivanovich (2018, 2018)
Title screen